EFFECT OF LOW LEVEL OF MINERAL PHOSPHORUS AND MEDIUM LEVEL OF NITROGEN ON PLANKTONIC PRODUCTIVITY AND INCREASE IN FISH PRODUCTION - M. Hussain; S. M. Hussain; M. Afzal; A. Javid; S. Abdullah; S. A. Raza; M. Iqbal (Journal of Animal and Plant Sciences, 2011)
A field trial was conducted to see the effect of low level of mineral phosphorous and medium level of nitrogen on the planktonic productivity and increase in fish production. Earthen ponds, each having dimension of 30×16×2m; area, 0.048 ha, were stocked with fish viz. Hypophthalmichthys molitrix, Labeo rohita and Cyprinus carpio at ratio 65: 20: 15, respectively. The treatment pond was fertilized with phosphorus and nitrogen @ 0.06% and 0.12% of wet fish body weight dayˉ1 while reference / control pond was not fertilized with phosphorus and nitrogen. Water samples were collected fortnightly for qualitative and quantitative estimation of plankton and showed four genera of Chlorophyceae, one genera of Chrysophyceae and three genera of Bacillariophyceae. Among zooplanktons, the Ciliates, Keratella, Cyclops and Daphnia were found maximum in the treated pond while very poor in the reference pond. The difference between treated and control pond for the production of planktonic biomass was statistically significant at p<0.05. The significant impact of treatment on planktonic productivity enhanced the fish production significantly higher in treated pond.
Keywords: Phosphorus; nitrogen; planktonic biomass; fish.